Arabinoxylan from wheat bran: molecular degradation and functional investigation. (October 2020) - Liu, Yan; Wang, Shaowei; Kang, Ji; Wang, Nifei; Xiao, Meng; Li, Zhenjing; Wang, Changlu; Guo, Qingbin; Hu, Xinzhong
Abstract: Ultrasonication, xylanase and trifluoroacetic acid (TFA) treatments were applied to modify wheat bran arabinoxylan (AX) molecules. Molecular weight (Mw) distribution analysis, methylation analysis, rheological analysis and starch in vitro digestibility test were followed to compare the structural and functional properties of AX under different treatments. Different degradation methods decreased the Mw of AX in distinct manners, resulting in fractions with different structural features. Ultrasound treatment decreased the Mw of AX (640 kDa) to medium size range (640–100 kDa) with a slightly decreased degree of branching (DOB). Xylanase and TFA treatments could generate fragments with relative lower Mw (<100 kDa) compared to ultrasound treatment. However, sugar residues of AX from xylanase treatment showed a much higher DOB (47.89) and better solubility than those from TFA treatment. AX of larger Mw fractions showed higher apparent viscosity under the shear rate (50.3/s) close to the value induced by gastrointestinal peristaltic. In vitro digestion experiments of AX-starch mixture and AX fortified bread both showed that the higher Mw of the AX demonstrated a better inhibitory effect against starch digestibility, leading to a higher percentage of resistant starch. According to differential scanning calorimetry (DSC) analysis, AX could inhibit the retrogradation of wheat starch during bread storage, which provides complementary information for the above-mentioned conclusions. Graphical abstract: Image 1 Highlights: Three arabinoxylan fractions with different molecular weight were obtained. The structural and functional features of different fractions were investigated. All fractions showed inhibition on in vitro digestibility of starch and bread. All fractions could inhibited the retrogradation of bread during storage.